Liver‐enriched transcription factor expression relates to chronic hepatic failure in humans. Issue 5 (23rd March 2018) - Guzman‐Lepe, Jorge; Cervantes‐Alvarez, Eduardo; Collin de l'Hortet, Alexandra; Wang, Yang; Mars, Wendy M.; Oda, Yoshinao; Bekki, Yuki; Shimokawa, Masahiro; Wang, Huanlin; Yoshizumi, Tomoharu; Maehara, Yoshihiko; Bell, Aaron; et al.
Abstract : The mechanisms by which the liver fails in end‐stage liver disease remain elusive. Disruption of the transcription factor network in hepatocytes has been suggested to mediate terminal liver failure in animals. However, this hypothesis remains unexplored in human subjects. To study the relevance of transcription factor expression in terminal stages of chronic liver failure in humans, we analyzed the expression of liver‐enriched transcription factors (LETFs) hepatocyte nuclear factor (HNF)4α, HNF1α, forkhead box protein A2 (FOXA2), CCAAT/enhancer‐binding protein (CEBP)α, and CEBPβ. We then selected downstream genes responsible for some hepatic functions (ornithine transcarbamylase [OTC], cytochrome P450 3A4 [CYP3A4], coagulation factor VII [F7], cadherin 1 [CDH1], phospho‐ezrin (Thr567)/radixin (Thr564)/moesin (Thr558) [p‐ERM], phospho‐myosin light chain [p‐MLC], low‐density lipoprotein receptor‐related protein 1 [LRP1]) in liver tissue from patients at different stages of decompensated liver function based upon Child‐Pugh classification, Model for End‐Stage Liver Disease score, and degree of inflammatory activity/fibrosis. We first examined differential expression of LETF and determined whether a relationship exists between transcript and protein expression, and liver function. We found HNF4α expression was down‐regulated and correlated well with the extent of liver dysfunction ( P = 0.001), stage of fibrosis ( P = 0.0005), and serum levels of total bilirubin ( P = 0.009; r = 0.35), albumin ( P < 0.001; r = 0.52), and prothrombin time activity ( P = 0.002; r = 0.41). HNF4α expression also correlated with CYP3A4, OTC, and F7 as well as CDH1 RNA levels. The Rho/Rho‐associated protein kinase pathways, which have been implicated in the regulation of HNF4α, were also differentially expressed, in concert with LRP1, a reported upstream regulator of RhoA function. Conclusion: HNF4α and other members of the LETFs appear to be important regulators of hepatocyte function in patients with chronic hepatic failure. ( Hepatology Communications 2018;2:582‐594)